Scenario on Indonesian Coal Governance - Pramono, Sidik; Irfan Ridwan Maksum,; Andreo Wahyudi Atmoko, (Technium Social Sciences Journal, 2021)
Coal as a non-renewable natural resource is still an important source of energy for Indonesia and is projected to continue into the future. The System Dynamics simulation shows that in 2030, Indonesia is predisposed to experiencing market failure, namely a gap between supply and demand, if referencing only to existing reserves and current production capacity that tends to increase from year to year. The governance of Indonesian coal is a multi-faceted governance whereby various policies, norms, and behavioral patterns as interactions between government, business actors, and communities, either individually or together, can influence the governance of Indonesian coal and which therefore necessitates alternative scenarios to take these factors into account. An ideal alternative scenario is a balance between “the gas pedal and brake”, as current improvements thus far cannot only be focused on a single aspect or factor. Production capacity must be controlled, whereby level of coal production is prioritized to meet domestic needs first. Next, the allocation of coal for export must be limited. The opportunity to increase export capacity is open when domestic needs have been fulfilled and domestic market capacity has reached a positive point, which is projected to occur after 2040.